GAMBARAN KLINIS DAN KOMPLIKASI PASIEN DEMAM BERDARAH DENGUE DERAJAT III DAN IV DI BAGIAN PENYAKIT DALAM RSUD ARIFIN ACHMAD PROVINSI RIAU PERIODE 1 JANUARI 2012 – 31 DESEMBER 2013 - Vivin Leovani; Ligat Pribadi Sembiring Pribadi Sembiring; Winarto " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTDengue hemorrhagic fever (DHF) is an infectious disease that can arise as a result of secondary infection by dengue virus. The severity of DHF is at grade III and IV. Pathological manifestations of organ systems can cause complications. This research is to determine the clinical features and complications of dengue patients in grade III and IV internist unit at Arifin Achmad Riau Province Hospital at period 1 January 2012 – 31 December 2013 with retrospective descriptive study of cross-sectional approach. Based on the results of the study, found 32 (4.6 %) patients with grade III and IV DHF than 702 dengue patients, consisting of 22 (68.75%) patients with DHF grade III and 10 (31.25%) patients with grade IV. Dengue patients at grade III and IV, there were 13 (40.6%) patients as a sample of 6 patients in 2012 and 7 patients in 2013. All DHF patients at grade III and IV has a fever, thrombocytopenia and increased hematocrit. Other clinical signs and symptoms found is narrowed pulse pressure (68.8%), rapid and weak pulse palpable (62.5%), petechiae (59.4%), hypotension (56.3%), melena (46, 9%), bleeding gums (37.5%), cold and moist extremities (28.1%), hematemesis (21.9%), epistaxis (12.5%), blood pressure was not measured (3.1%). Complications found that liver abnormalities (69.2%), liver disorders and acute renal failure (23.1%), and liver disorders, acute renal failure and encephalopathy (7.7%) of 13 patients.Keywords: dengue fever, complications, clinical features